PUSAT INFORMASI GEOPARK MERATUS DI BANJARBARU - Cahyadi, Muhammad Rizqon; Aufa, Naimatul (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2022)
The Meratus Geopark is a government program to preserve the Meratus Mountains. These mountains stretch from the southeast to the northwest of South Kalimantan Province. These mountains have biodiversity and non-biological diversity which in recent years has been massively exploited to the point of environmental degradation. To reduce and anticipate environmental damage, the local government cooperates with various parties to initiate the Meratus Geopark program. In 2019, Geopark Meratus succeeded in becoming part of Geopark Indonesia, but until now there is no Meratus Geopark Information Center available. The Meratus Geopark Information Center is planned to be built in Pumpung Cempaka Village which is known as one of the largest diamond mining villages in South Kalimantan. The architectural problem to be solved is "How is the design of the Meratus Geopark tourism information and research center that is able to become a center for geological studies as well as being able to educate the public to participate in preserving the natural environment of the Meratus Mountains?". To solve this problem, the Mawaris Meratus concept was initiated as an effort to raise awareness and educate the public to protect Meratus' wealth. This concept is realized by using the active learning method. This design resulted in the Meratus Geopark Information Center which educates the public to take a role in preserving and inheriting the natural environment of the Meratus Mountains.